(untitled) (Applied Biological Research, 2020)
Pedigree information data for 49 years (1969-2017) for fitness traits maintained at Mountain Research Centre for Sheep and Goat (MRCSG), SKUAST-K Shuhama Kashmir was analyzed to evaluate the performance of Corriedale sheep under the temperate agro-climatic conditions of Jammu & Kashmir state. The effects of non-genetic factors such as period of birth and sex on various normalized fitness traits such as age at first lambing (AFL), litter size (LS), total lambs born perewe (TLB) and survival rate (SR) were analyzed by least squares analysis. The period of birth was found to have highly significant (p < 0.01) effect on all the traits studied. The least square means revealed that lambs born in period 1969- 1975 had higher values of TLB, higher percentage of SR and lowest value of ALF. Sex of lamb had significant (p < 0.05) effect on SR. The heritability estimates were 0.09 ± 0.01, 0.40 ± 0.04, 0.29 ± 0.07 and 0.23 ± 0.03 for AFL, LS, TLB and SR, respectively. The study revealed that AFL and fitness traits are influenced by both genetic and non-genetic factors. Therefore, improvement in these traits in the flock can be achieved through selection and management.